2006
DOI: 10.1080/14992020600957335
|View full text |Cite
|
Sign up to set email alerts
|

Acquired profound hearing loss: Mental health and other characteristics of a large sample

Abstract: The study investigated the mental health and other characteristics of people with acquired profound hearing loss (APHL) and contrasted this group with acquired hearing loss (AHL) in general. A survey was completed over the internet by 95 adults and by 27 people who had attended a one-week course of rehabilitation. The latter group completed questionnaires of anxiety and depression, post-traumatic stress, and hearing handicap. The survey covered a wide range of factors associated with the history of hearing los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
44
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 16 publications
6
44
0
4
Order By: Relevance
“…The impairments we observed in musical emotion ratings were not accounted for by depressive disorders that often affect profoundly deaf subjects (Hallam et al, 2006; Garnefski and Kraaij, 2012). The STAI (Spielberger, 1983) and POMS (McNair et al, 1992) questionnaires revealed there to be no difference between CI and NH participants, which indicates that depression or anxiety disturbances did not interfere with judgments of musical emotion.…”
Section: Discussionmentioning
confidence: 56%
“…The impairments we observed in musical emotion ratings were not accounted for by depressive disorders that often affect profoundly deaf subjects (Hallam et al, 2006; Garnefski and Kraaij, 2012). The STAI (Spielberger, 1983) and POMS (McNair et al, 1992) questionnaires revealed there to be no difference between CI and NH participants, which indicates that depression or anxiety disturbances did not interfere with judgments of musical emotion.…”
Section: Discussionmentioning
confidence: 56%
“…All three of the most employed tactics focus on physical closeness to the speaker and observation of a speaker ' s face, expressions, gestures, or lips. However, there is greater emphasis on the lips in the severe group, consistent with the employment of speech reading by this group (Hallam et al, 2006).…”
Section: Frequency Of Use As a Function Of Self-reported Hearing Impamentioning
confidence: 74%
“…Examples of psychological and social effects are depression, loneliness, and social isolation (Kramer et al, 2002;Nachtegaal et al, 2009b). Emotional functioning may be disturbed by distress and anxiety due to hearing impairment (Kramer et al, 2002;Tambs, 2004;Hallam et al, 2006;Nachtegaal et al, 2009b). Physiological reactions may also occur.…”
Section: Sumariomentioning
confidence: 97%
“…Given the elevated level of depressive symptoms, distress, or somatization in people with hearing impairment found in previous studies (Kramer et al, 2002;Tambs, 2004;Hallam et al, 2006;Nachtegaal et al, 2009b), and the relationship of these variables with higher levels of health care use (e.g. Grabe et al, 2009), it was expected that individuals with hearing impairment would have made more use of psychosocial care.…”
mentioning
confidence: 97%